Development and Characterization of Innovative Two-Layer Knitted Fabrics for Outerwear (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This study presents the development and analysis of innovative two-layer knitted fabrics intended for outerwear, focusing on expanding fabric types, reducing raw material consumption, and enhancing product quality. Three variants of these fabrics were knitted using a 12th-class flat two-needle knitting machine (Long Xing LXA 252). Polyacrylonitrile yarn with a linear density of 32x2 tex and electrically conductive yarn were used as primary materials. The research evaluates how fabric structure and production methods affect technological parameters such as air permeability, tensile strength, elongation at break, abrasion resistance, and deformation characteristics. Findings highlight that structural adjustments and material compositions significantly improve the fabric's functional and aesthetic qualities, ensuring better consumer properties.